Mengembangkan Video Pembelajaran Remedial Matematika Berbasis Online di SMP - Nabila, Raisa; Syamsuddin, Nuralam (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Students' low understanding results in low test scores obtained by students and not reaching the specified KKTP (Criteria for Completion of Learning Objectives) so that these students are considered incomplete. The remedial implementation strategy can be implemented by re-learning with different, better methods and media. In this digital era, the potential for using technology in learning is very large. By utilizing online-based learning media, such as interactive learning videos, students can be more actively involved in the remedial learning process. Therefore, researchers want to develop learning media in the form of online-based remedial learning videos. This research is development research that follows the stages of the ADDIE development model. The data analysis techniques used in this research are validation data analysis techniques and practicality test data analysis. The research results showed that the learning videos developed were valid with an assessment of 71% by media experts and 87.5% by material experts, in the good category. Therefore, the process and results of developing online-based remedial learning videos have great potential to become digital-based learning videos that can be used in remedial learning.